The FlhD/FlhC complex, a transcriptional activator of the Escherichia coli flagellar class II operons. - Liu, X (1994)
The Escherichia coli flhD operon encodes two genes, flhD and flhC. Both gene products were overproduced and purified. The purified proteins formed a complex consisting of two FlhD and two FlhC molecules. Mobility shift assays showed that the FlhD/FlhC complex had a DNA-binding activity and bound to the upstream regions of fliA, flhB, and fliL operons (class II), which are under direct control of the flhD operon. DNase I footprinting analyses of FlhD/FlhC binding to the three class II promoter regions revealed protection of a 48-bp region of the fliA operon between positions -41 to -88, a 50-bp region of the flhB operon between positions -28 to -77, and a 48-bp region of the fliL operon between positions -29 to -76. In vitro transcription experiments demonstrated that the FlhD/FlhC complex is a transcriptional activator required for the transcription of the three class II operons examined in vitro.